Pharmacokinetics Interaction and Biodistribution of 5 Fluorouracil with Radiopharmaceuticals 99mTc Glutathione for Cancer Diagnostic in Mice Cancer Model - Kurniawan, Ahmad; Ambar Wibawa, Teguh Hafidz; Daruwati, Isti; Iswahyudi, Iswahyudi (Indonesian Journal of Pharmacy, 2019)
Radiopharmaceutical 99mTc-Glutathione has been developed for cancer diagnostic in nuclear medicine. Interactions between chemotherapy drugs and radiopharmaceuticals can altered radiopharmaceuticals performance.  Drug interaction 5-fluorouracil (5-FU) with a radiopharmaceutical 99mTc-Glutathione in mice cancer model has been proven in pharmacokinetics study. The biological half-life distribution of 99mTc-Glutathione for cancer model mice when administrated with 5-FU become longer to 0.340±0.121h if compared with 99mTc-Glutathione. Biological half-life elimination for cancer model mice given with 99mTc-Glutathione is 72.712±2.427h. Administration of 5-FU makes the biological half-life elimination of 99mTc-Glutathione shorter to 17.030±3.459h. Biodistribution study of 5-FU continued with 99mTc-Glutathione for cancer model mice showed higher physiological uptake in the kidney was observed (39.77±2.70%ID/g) for 99mTc-Glutathione has lower uptake on kidney (29.55.3.73 %ID/g) with p<0.05. Based on calculation on cancer model mice with colon cancer compared with muscle, shown target/non-target (T/NT) ratio 2.93 for 5-FU continued with 99mTc-Glutathione has ratio 0.42. Low ratio T/NT may affect to poor organ visualization for cancer diagnosis.  Acute toxicity study has shown drugs safety for clinical purpose. The knowledge about chemotherapy drug interaction with a radiopharmaceutical is important to have a correct diagnosis of the patient on clinical application.